2020
DOI: 10.3389/fneur.2020.575811
|View full text |Cite
|
Sign up to set email alerts
|

Patients and Health Professional's Perspective of Functional Mobility in Parkinson's Disease

Abstract: Results: All participants were able to provide a spontaneous definition of FM, matching with the proposed concept. All agreed that PD affects patient's FM, increasing the limitations with disease progression, and with the existence of a serious prejudice with walking aids that hinders its use. Early-stage patient's perspective seems to be more in line with neurologist's perspective, while the views of advanced-stage patients were closer to physiotherapist's views. Conclusion:FM concept was considered as intuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The previous literature showed that patients valued functional mobility for being a meaningful outcome that is easy to describe. Health professionals find it a useful outcome to facilitate patients’ abilities to describe their disability and to help clinicians adopt a more patient-centered approach and to provide individualized care [ 38 ]. The TUG test is the gold-standard outcome measure to evaluate functional mobility in PD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous literature showed that patients valued functional mobility for being a meaningful outcome that is easy to describe. Health professionals find it a useful outcome to facilitate patients’ abilities to describe their disability and to help clinicians adopt a more patient-centered approach and to provide individualized care [ 38 ]. The TUG test is the gold-standard outcome measure to evaluate functional mobility in PD [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise therapies have shown good results in PD, as rehabilitation and maintenance of physical and functional capacities are crucial aspects in these patients [6]. In PD management, physiotherapy is mainly an exercise-based intervention that addresses five core areas: physical fitness, transfers, manual activities, balance, and gait [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus on functional mobility as an outcome of interest in KAFO therapy is the originality of this review, since the previous review study reported walking ability in an experimental setting, using a motion capture system or electromyography, as an outcome of KAFO therapy ( 8 ). Functional mobility is important for patients, to enable participation in ADL in the real-life setting by addressing orthotic therapy ( 2 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Improving functional mobility and activities of daily living (ADL) in patients with stroke are important aims of rehabilitation ( 1 ). Functional mobility is the capacity of a person to move from one place to another in order to participate in ADL, which includes movements such as standing, walking, and transferring ( 2 ). Ankle–foot orthosis (AFO) ( 3 , 4 ), functional electrical stimulation (FES) ( 5 ), trunk training ( 6 ), and physical fitness training ( 7 ) are considered useful interventions to improve functional mobility in patients with stroke.…”
mentioning
confidence: 99%